LIBERTÀ RELIGIOSA, PRIVACY E SICUREZZA DEI LUOGHI DI CULTO TRA SOFT LAW E HARD LAW (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Religious freedom, privacy and security of places of worship between soft law and hard lawThe contribution examines the impact of the monitoring and control activities of places of worship on the free exercise of the right to religious freedom and on the right to the protection of personal data in the light of the OSCE’S Policy Guidance on Freedom of Religion or Belief and Security and EU Quick Guide to support protection of Places of Worship. The paper also highlights the reversal, in OSCE’S Policy Guidance and in the UE Quick Guide, of the securitarian approach that characterizes some legal provisions concerning freedom of worship and religious sites and it finally underlines the importance of the enhancement of soft law instruments’ interpretative function in the constitutional Courts’ control of legitimacy of the laws and acts having the force of law to guarantee individual fundamental rights.